Utilization and Satisfaction With Major Health Care Services Amongst the Slum Dwellers of Dhaka City (Journal of Chittagong Medical College Teachers' Association, 2014)
The main objectives of this study are to find out the extent of utilization of health care services and satisfaction with major types of health care services amongst the slum dwellers of Dhaka city. This descriptive cross sectional study was conducted for a period of 6 months starting from July 2013 to December 2013. A house to house survey was conducted and a total of 1029 slum dwellers were enrolled for the study. Purposive sampling technique was used in the study. Data were collected through pre-tested and semi-structured questionnaire. The study showed that pharmacy quacks 476 (46.3%) were the most dominant source of health care for the slum dwellers in Dhaka city. Medical College Hospital 238 (23.1%) was the second most dominant source of health care in slum areas. The other main sources were government hospitals, private practitioners respectively. Most of the respondents 429 (41.69%) were satisfied with the services of pharmacy quack and 268 (26.04%) respondents were satisfied with the services of medical college hospital. Among rest, 132 (12.82%) were satisfied with government hospitals and 121(11.75%) were satisfied with private practitioners. Majority of the respondents selected pharmacy quack to receive health care services due to affordability 127 (24.6%) and feasibility 107 (20.7%). In the study, 51 (16.1%) respondents selected medical college hospital for availability of facilities, effective treatment, good doctor-patient communication and better investigation facilities. According to the respondents 291 (38.1%) the main barrier to access health care was treatment cost. Highly significant association was found between educational status of the slum dwellers and selection of pharmacy quack (p=0.000) and medical college hospital (p=0.000). Significant association was also found between occupational status and selection of pharmacy quack (0.003) and medical college hospital (0.011). Highly significant association was found between monthly income and selection of medical college hospital (p=0.000). Pharmacy quack was the most dominant healthcare service in slum area. As persons running pharmacy quacks often provide poor quality of healthcare services, they need continuous training and back-up supports to improve their quality of services and to strengthen the overall healthcare system in Bangladesh.JCMCTA 2014 ; 25 (2) : 7-13